2016
DOI: 10.1002/jmri.25250
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantitative intravoxel incoherent motion parameters in the preoperative diagnosis of nodal metastasis in patients with rectal carcinoma

Abstract: An IVIM sequence may be helpful in diagnosing metastatic lymph nodes of rectal carcinoma. Average D and ADC values are more sensitive than f and D* values in this differentiation. J. MAGN. RESON. IMAGING 2016;44:1031-1039.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
4
23
1
Order By: Relevance
“…The diffusion parameters obtained in this analysis for the ADC, IVIM, and Kurtosis models, i.e. higher ADC and D and lower D* and k in malignant nodes, are consistent with 2 recent studies employing IVIM and Kurtosis, respectively, to image lymph nodes in patients with rectal cancer, however, in contradiction to the IVIM results from Ref. 29, in which the diffusivity in the malignant nodes is lower.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The diffusion parameters obtained in this analysis for the ADC, IVIM, and Kurtosis models, i.e. higher ADC and D and lower D* and k in malignant nodes, are consistent with 2 recent studies employing IVIM and Kurtosis, respectively, to image lymph nodes in patients with rectal cancer, however, in contradiction to the IVIM results from Ref. 29, in which the diffusivity in the malignant nodes is lower.…”
Section: Discussionsupporting
confidence: 88%
“…To separate the effects of tissue perfusion and diffusion, the intravoxel incoherent motion (IVIM) captures the fast signal decay at low b ‐values due to flow effects, and in many cases it provided better tumor characterization compared to ADC . For rectal cancer, IVIM also improved lymph node differentiation, although the results are not consistent between the 2 studies. Combining IVIM and kurtosis can provide insight into both perfusion and non‐Gaussian diffusion effects and has shown potential for differentiating various tumors as well as lymph nodes in the head and neck region; however, to our knowledge it has not been employed thus far to image lymph nodes involved in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…D app and ADC values of metastatic LNs were significantly greater than those of benign LNs. An earlier study from another group also demonstrated that the D and ADC values from intravoxel incoherent motion were significantly higher in metastatic LNs [18]. The greater D value of metastatic nodes in the earlier study might be accounted for by low cellular density, and the heterogeneity of metastatic nodes may be partly caused by the presence of necrotic tissue in the nodes [19].…”
Section: Discussionmentioning
confidence: 60%
“…As one of the latest MRI technologies, IVIM is more and more widely applied in the study of various human organs. In recent years, some studies have used IVIM to identify benign and malignant tumours (14,15), and the peritoneal lymph node metastasis of rectal cancer (16,17). However, the application of IVIM in the diagnosis of mediastinal lymph node metastasis of lung cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%